2009
DOI: 10.1088/1748-0221/4/03/p03012
|View full text |Cite
|
Sign up to set email alerts
|

Pixel detectors for x-ray imaging spectroscopy in space

Abstract: Pixelated semiconductor detectors for X-ray imaging spectroscopy are foreseen as key components of the payload of various future space missions exploring the x-ray sky. Located on the platform of the new Spectrum-Roentgen-Gamma satellite, the eROSITA (extended Roentgen Survey with an Imaging Telescope Array) instrument will perform an imaging all-sky survey up to an X-ray energy of 10 keV with unprecedented spectral and angular resolution. The instrument will consist of seven parallel oriented mirror modules e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…36,37 The future needs of 2D X-ray detectors for the European Free Electron Laser in Hamburg were briefly discussed by Graafsma, 38 who identified a clear need for a new generation of 2D detectors. The needs of the space community for high performance pixellated detectors was described by Treis et al, 39 who identified the novel dual energy pixellated X-ray detector for the SIMBOL-X instrument on a novel multi-satellite high performance X-ray telescope. This instrument comprised a 128 Â 128 DEPFET (depleted P-channel field effect transistor) pixel array for the lower energies and a pixellated CdTe detector for the higher energies of up to 80 keV.…”
Section: Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 The future needs of 2D X-ray detectors for the European Free Electron Laser in Hamburg were briefly discussed by Graafsma, 38 who identified a clear need for a new generation of 2D detectors. The needs of the space community for high performance pixellated detectors was described by Treis et al, 39 who identified the novel dual energy pixellated X-ray detector for the SIMBOL-X instrument on a novel multi-satellite high performance X-ray telescope. This instrument comprised a 128 Â 128 DEPFET (depleted P-channel field effect transistor) pixel array for the lower energies and a pixellated CdTe detector for the higher energies of up to 80 keV.…”
Section: Detectorsmentioning
confidence: 99%
“…Geochemical discrimination and cluster and discriminant analysis was used to distinguish 13 well-known Roman basaltic lava quarries in the East and West Eifel volcanic fields and so to provenance millstones to a specific quarry with a specified degree of confidence. Linthout et al 340 used petrographic and XRF analysis and 40 Ar/ 39 Ar dating to provenance basaltic blocks from Roman sites at Vleuten-De Meern, The Netherlands. The origin was deduced to be sites in Germany with transport facilitated by a now sanded up branch of the Rhine.…”
Section: Archaeological Cultural Heritage and Forensicmentioning
confidence: 99%
“…Although the e-Rosita telescopes will have a total area of CCDs about an order of magnitude greater than present generation X-ray instruments, the pixel size will be larger to match the telescopes and the number of pixels will be only just over 10 6 [79]. Instruments planned for the IXO X-ray observatory are also in the few megapixel range, though a single monolithic device will cover 100 cm 2 [80].…”
Section: Field Of Viewmentioning
confidence: 99%
“…The effective area of the SXI and overall sensitivity (Table 3) is approximately that of one PN telescope on XMM-Newton, so that it is approximately 10X more sensitive than the XRT on Swift. The focal plane camera design is a 384 x 384 pixel array with 75/80 m pixels depending on whether it is a CCD (e2V) or DEPFET (MPE) detector as planned for eROSITA and possibly IXO (Treis et al 42 ). Either camera could be operated at -50C with only passive cooling though a thermo-electric cooler would be provided to minimize solar constraints.…”
Section: Soft X-ray Imager (Sxi)mentioning
confidence: 99%